Free-form anisotropy: A new method for crack detection on pavement surface images - Tien Sy Nguyen; Begot, S.; Duculty, F.; Avila, M. (2011 18th IEEE International Conference on Image Processing, 2011)
This paper presents a new measure which takes into accounts simultaneously brightness and connectivity, in the segmentation step, for crack detection on road pavement images. Features which are calculated along every free-form paths provide detection of cracks with any form and any orientation. The method proposed does not need learning stage of free defect texture to perform default detection. Experimental results were conducted on some samples of different kinds of pavements. Results of the method are also given on other kinds of images and can provide perspectives on other domains as road extraction on satellite images or segment blood vessels in retinal images.